Interactions between employment and training policies - Frank Oskamp; Dennis J. Snower (Kiel Institute for the World Economy (IfW), 2007)
This paper examines the interactions between employment and training policies. Their effectiveness in stimulating income may be interdependent for various important reasons. For example, the more employment policies stimulate the employment rate, the greater the length of time over which workers use the human capital generated by training policies. Moreover, the greater the government expenditures on employment and training subsidies, the higher the taxes required to finance these expenditures and these higher taxes reduce aggregate income. On account of such effects, employment and training policies may be complementary or substitutable with respect to aggregate income. To analyze these interactions, we construct a simple, dynamic model of hiring decisions, derived from microfoundations. The model is calibrated with German data. Surprisingly, the simulation shows that, for reasonable parameter values, the complementarities are weak or absent. The analysis provides a methodology for examining policy interactions which may be useful well beyond the bounds of employment and training policies.
Keywords: J68; J24; J23; J64; J21; 330; Hiring subsidies; Training subsidies; Vocational training; Employment; Unemployment; Complementarities; Arbeitsmarktpolitik; Berufsbildungspolitik; Komplementärgut; Wirtschaftspolitische Wirkungsanalyse; Arbeitsnachfrage; Beschäftigungseffekt; Theorie; Deutschland